Comprehensive Physiology 2014
DOI: 10.1002/cphy.c130041
|View full text |Cite
|
Sign up to set email alerts
|

Vestibulo‐Sympathetic Responses

Abstract: Evidence accumulated over 30 years, from experiments on animals and human subjects, has conclusively demonstrated that inputs from the vestibular otolith organs contribute to the control of blood pressure during movement and changes in posture. This review considers the effects of gravity on the body axis, and the consequences of postural changes on blood distribution in the body. It then separately considers findings collected in experiments on animals and human subjects demonstrating that the vestibular syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
130
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 313 publications
(490 reference statements)
3
130
0
Order By: Relevance
“…This information is conducted centrally to control eye position, balance, blood pressure and heart rate (Uchino and Kushiro, 2011; Yates et al, 2014). Hair cell function is dependent upon the development of a polarized structure called the stereociliary bundle, the orientation of which is tightly coordinated between neighboring cells.…”
Section: Introductionmentioning
confidence: 99%
“…This information is conducted centrally to control eye position, balance, blood pressure and heart rate (Uchino and Kushiro, 2011; Yates et al, 2014). Hair cell function is dependent upon the development of a polarized structure called the stereociliary bundle, the orientation of which is tightly coordinated between neighboring cells.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in detail in a recent review (32), considerable evidence from experiments in both human and animal subjects has shown that the vestibular system participates in regulating sympathetic nervous system activity, to provide for adjustments in blood pressure during movement.…”
Section: Organization Of Vestibulospinal and Vestibulosympathetic Patmentioning
confidence: 99%
“…Neurons in the RVLM that control sympathetic nervous system activity receive vestibular inputs through a variety of pathways (32), as illustrated in Figure 1. Since many of the relays from the vestibular nuclei to the RVLM are polysynaptic, it is difficult to identify “vestibulosympathetic neurons” during neurophysiologic experiments.…”
Section: Inputs To Vestibulospinal and Vestibulosympathetic Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter projections inform central pre-sympathetic autonomic nervous system neurons influencing blood pressure, respiration and gastrointestinal activity about changes in posture and body position with regard to gravity. Collectively, these functional pathways are referred to as the vestibulo-sympathetic reflex (VSR) (Yates et al 2014). …”
Section: Introductionmentioning
confidence: 99%